(3CfhGQ GdabGgIs - (3GdLfGMj, GdfLaj, cGTa GdZWGA, MSf Hf LYaQ Hf NVQ, J (B1262 (3g`s
(3ChdgG (B:s
... (3cJGH GdWgGQI hgj dZI GdfRGgI hGdfXGaI ef GdbPQGJ GdMSjI hGdfLGSGJ GdXGgQjI hJSJYed cKjQG aj GdcJGH hGdSfI aj GdfRGgI ef GdCOfGS GdeYfhjI hGdCQLGS GdHGWfjI Ydi hLg GdGTJQGc GdeYfhj (B...s
(3BNQgG (B:s
... (3hGMJed GdHWdGf dJYdb Gdfgj HGdebOeI adG jchf (B... (3ajaSO dYOe JYdb GdCeQ Gh dGf faS GdhVhA GSJYeGd (B... (3hGdGNjQ GMhW hGdGhd Cbhi Je cJGH GdWgGQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B1\543s
(3GdPQjYI (B2 - 244( 1702)s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis